Electronic Surveillance System in Light of Developments in Criminal Procedural Systems Under Order 15-02 - Darrar, Abdelhadi (Journal of Legal Studies and Researches, 2017)
The amendment to the Code of Criminal Procedure included provisions for the use of electronic monitoring, specifically the electronic bracelet, as a judicial supervision measure and as an alternative to pretrial detention—a long-standing problem in the Algerian justice system. Experience has demonstrated the effective role of electronic monitoring in mitigating the adverse effects of custodial penalties. Order 15-02 assigned the authority to place a defendant under electronic monitoring to the investigating judge, by imposing measures on the wearer of the bracelet (the convicted individual) to ensure compliance. Jurisprudential opinions have been divided, with some supporting and others opposing the system, considering its advantages and drawbacks. If implemented effectively in practice, the electronic monitoring system will inevitably contribute positively to the development of the judicial system in Algeria.